Nieoficjalne nazwy szkół ponadgimnazjalnych - Jachimowska, Katarzyna (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
This article registers and describes non oficial names of secondary schools, made by teenage community. Analysed lexical innovations reveal affinity to the group, which uses “its” language called by linguists youth slang, sociolekt, pupils or teenage lingo or pupils jargon. Examined formative neologisms reflect general development tendencies of the language – tendency for efficiency, which is realised in tendency for using acronims and tendency for creating expressive forms. The article emphasises that non oficial names are created not only for naming purposes but mainly pragmatic ones. In the thesis few reflections are shown which are linked to correctness of analysed secondary names, as there are doubts as to the correctness of their spelling and lexical-semantic cohesion.